PENERAPAN MODEL PROBLEM BASED LEARNING PADA MATA PELAJARAN IPS DI KELAS VII SMP NEGERI 3 PONTIANAK - Ningtias, Marani Cahya; Buwono, Sri; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research in this thesis aims to determine the Learning Outcomes of Problem Based Learning Models in Social Studies of Class VII Students of Junior High School 3 Pontianak. The research method used in this research is Experiment with True Experimental design and Posttest-only control design. Techniques Data collectors are carried out through observation and tests. Data collection tool used is the observation sheet (Check List), and Post-Test. The results of this study indicate that: 1) Learning outcomes of social studies students in class VII SMP Negeri 3 Pontianak in the experimental class using the Problem Based Learning model obtained a percentage of 92% the average score of 18.28. 2) Students' learning outcomes in social studies subjects in class VII SMP Negeri 3 Pontianak in the control class using the model number head together obtained a percentage of 75% average score of 17.11. 3) Problem-Based Learning Model can improve learning outcomes in IPS Subject Students Class VII SMP Negeri 3 Pontianak can be seen from Effect Size Problem Based Learning Model on IPS Subjects Students Class VII SMP Negeri 3 Pontianak of 0.61 included in the category of being. Â Keywords: Problem Based Learning Model, Social StudiesÂ